Improving the Properties of Polysaccharide-Based Films by Incorporation of Polyphenols Through Free Radical Grafting: A Review - Karla Hazel Ozuna-Valencia; Francisco Rodríguez-Félix; Enrique Márquez-Ríos; María Jesús Moreno-Vásquez; Abril Zoraida Graciano-Verdugo; Miguel Ángel Robles-García; Santiago Pedro Aubourg-Martínez; Idania Emedith Quintero-Reyes; Betzabe Ebenhezer López-Corona; José Agustín Tapia-Hernández (Polysaccharides, 2024)
The increasing demand for sustainable materials has propelled research into polysaccharide modifications for various applications, particularly in active packaging. This review aims to explore the incorporation of bioactive compounds such as polyphenols into polysaccharides, focusing on chemical modification through free radical grafting techniques. The methods examined include enzymatic, physical, and chemical grafting techniques, highlighting their effectiveness in enhancing the properties of polysaccharide-based films. Recent studies have demonstrated that free radical grafting can significantly improve the mechanical, barrier, and antimicrobial properties of these films, extending their applicability in the food and pharmaceutical industries. However, challenges such as the stability of polyphenols and the understanding of grafting mechanisms remain critical areas for further investigation. This review discusses these advancements and outlines future research directions, emphasizing the potential of polysaccharide modifications to create innovative materials that meet the evolving needs of consumers and industries alike.